Análise das respostas fisiológicas e metabólicas entre dois tipos de treinamento em ratos wistar - Santos, Waleska dos (2019)
Physical training is an alternative to promoting health and maintaining well-being. Among the various types of training, there is continuous training and interval training, which have subdivisions and benefits established in the literature. In the middle of these trainings, there are the moderate continuum and the high intensity interval, which are studied in this research. Thus, it is important to evaluate the variables of body changes resulting from these physical exercises because, there are gaps about their effects mainly using the specific protocols of this research, thus enabling a more effective prescription. Thus, the general objective of this study was to analyze physiological and metabolic responses two types of training in Wistar rats. The specific objective was to analyze the eight-week physiological and metabolic responses of the High Intensity Interval Training (HIIT) and the Continuous Moderate Intensity (CM) in liquid medium of Wistar rats, by quantifying markers of tissue injury, oxidative stress and of the glycemic profile. A total of 24 rats divided equally into three groups were included: GSED (sedentary group), GHIIT (group that did HIIT) and GCM (CM). As a result, creatine kinase concentrations increased in GHIIT in relation to GSED, respectively (442.6 ± 8.35 U / I, 140.4 + 35.48 U / I, p = 0.019); lactate dehydrogenase was increased with training (HIIT and CM) in relation to GSED, respectively (250.9 + 70.67 U / I, 241.8 + 100,7 U / I, 112.8 + 28.08 U / L; p <0.01); non-oxidized hepatic sulfhydryl were increased in GHIIT compared to GCM, respectively (498.7 + 214.3 nmol / ml, 270.5 + 104.4 nmol / ml, p = 0.035); glycemia was more stable in GCM than GHIIT, respectively (p <0.01). It is concluded that the HIIT and CM protocols used in this study resulted in tissue injury responses, however, HIIT indicated an improvement in the adaptive capacity of antioxidant response, whereas CM a predominance of glycemic maintenance in Wistar rats.